Seasonal Variability and Trends of PM10 and PM2.5 Particulate Matter Pollution in Warsaw: A Multi-Year Analysis - Starzomska Aleksandra; Strużewska Joanna (Environmental Protection and Natural Resources)
The article examines the temporal variability and seasonal trends of PM10 and PM2.5 particulate matter pollution in Warsaw over six years from 2016 to 2021. The study utilizes data from air quality monitoring stations in various parts of Warsaw, including urban background and traffic stations. The analysis reveals distinct patterns in particulate matter concentrations, with higher levels observed during the colder months, particularly from January to March. Conversely, lower concentrations are recorded from June to August, in the summer. The study also highlights the influence of meteorological conditions and the heating season on air pollution levels. Statistical analyses demonstrate significant variability in pollution levels across different months and years, with the correlation between monitoring stations fluctuating over time. The findings provide valuable insights into the factors driving air pollution in Warsaw and underscore the importance of ongoing monitoring and mitigation efforts to improve air quality in urban environments.